Parenteral anticoagulants in heart disease: current status and perspectives (Section II). Position paper of the ESC Working Group on Thrombosis-Task Force on Anticoagulants in Heart Disease. - De Caterina, R; Husted, S; Wallentin, L; Andreotti, F; Arnesen, H; Bachmann, F; Baigent, C; Huber, K; Jespersen, J; Kristensen, S; Lip, G; Morais, J; et al. (2013)
Anticoagulants are a mainstay of cardiovascular therapy, and parenteral anticoagulants have widespread use in cardiology, especially in acute situations. Parenteral anticoagulants include unfractionated heparin, low-molecular-weight heparins, the synthetic pentasaccharides fondaparinux, idraparinux and idrabiotaparinux, and parenteral direct thrombin inhibitors. The several shortcomings of unfractionated heparin and of low-molecular-weight heparins have prompted the development of the other newer agents. Here we review the mechanisms of action, pharmacological properties and side effects of parenteral anticoagulants used in the management of coronary heart disease treated with or without percutaneous coronary interventions, cardioversion for atrial fibrillation, and prosthetic heart valves and valve repair. Using an evidence-based approach, we describe the results of completed clinical trials, highlight ongoing research with currently available agents, and recommend therapeutic options for specific heart diseases.